CONTENT ANALYSIS OF STUDENTS’ INTERNET COMMUNICATION WITH AUTHORITIES AND UNIVERSITY ADMINISTRATIONS TO STUDY PROBLEMS OF KAZAKHSTAN YOUTH (Journal of Philosophy Culture and Political Science, 2018)
Sociological surveys usually conducted to reveal the problematic issues that concern students sometimes are not suffice to show the most acute problems and concerns. Therefore, the authors of the article undertook to employ additional tools to collect the data on the issues faced by students today and on the means they trying to resolve them, namely the existing channels of communication with administrative figures of their universities and with the authorities. The article deals with most effective resources available for students at present such as the blogs of the Minister of Education and Science of the Republic of Kazakhstan and the blogs of Chancellors of a number of Kazakhstan universities. The authors argue that the blogs and websites are not only good alternative source for a research conducted in the aim to reveal the current sentiments and attitudes among students, they also will facilitate timely identification of the difficulties and problems faced by students today. The article discusses the reasons why students decide to post on the blogs of the Minister of Education and Science and those of the Chancellors of their universities. The quantitative analysis of the posts made by students on the blogs of the Minister of Education and Science and those of the universities Chancellors enabled to find out that only 0.001% of students throughout Kazakhstan are ready to raise openly their problems via electronic modes of communication. Among possible causes, the authors identify low level of students’ confidence in such communication modes and poor quality of the feedback received. The article depicts how the problems raised by students are reflected in the activities of the state. The content analysis of the Addresses of the President N. Nazarbayev to the Nation of the Republic of Kazakhstan, the blogs, and the inquiries made by the Members of the Parliament show that the main problems are overall improvement of the quality of education so that it would provide for training of professionals who are qualified enough to contribute into for the country’s economy, employment of the graduates, and the housing.Key words: student youth, ministry of education and science, deputies, blogs, problem students.